Association between higher coffee quality, bioactive chemical profile and sustainable practices - Viana, Gabriel Silva; Santana, Derielsen Brandão; Pereira, Luana de Almeida; Tieghi, Heloísa; da Silva, Vinicius Fortes; Ayer, Joaquim Ernesto Bernardes; Dias, Danielle Ferreira; Soares, Marisi Gomes; Chagas-Paula, Daniela Aparecida; Mincato, Ronaldo Luiz; Bueno, Paula Carolina Pires (Frontiers in Agronomy, 2025)
Coffee is one of the most vulnerable crops to climate change and farming practices, since its productivity is shaped by factors such as temperature, precipitation, and soil, among others. Consequently, the final product’s chemistry and quality can be significantly altered. This study investigates the hypothesis that higher coffee quality is associated with production areas implementing sustainable management practices. For that, we assessed the link between agricultural practices, sensory quality and bioactive chemical profile of coffee. Coffea arabica beans were sourced from two contrasting cultivation areas in Brazil. The changes in the chemical composition of the beans were assessed by targeted metabolomics, while the quality of the coffee was evaluated by sensory grading. Higher quality and higher altitudes correlated with lower levels of all xanthine alkaloids, ferulic acid and p-coumaric acid. Higher soil organic matter was associated with lower levels of trigonelline, theophylline, caffeine and ferulic acid. Interestingly, soil organic matter and organic carbon stock correlated positively with coffee quality. Therefore, this study demonstrates that promoting coffee production through sustainable practices contributes not only to the mitigation of effects of greenhouse gas emissions but also to the production of higher-quality coffees with increased added value.